Assessment of Pure Live Seed, Optimum Seeding Rate and Best Buy Value in Maize (Zea mays L.) - N. INDRAKUMAR SINGH,; J.S. CHAUHAN, (Seed Research, 2026)
The present study was conducted to assess the planting value, seeding rate and to find out the best buy value (real pay) of two maize varieties namely VIVEK HYBRID 9 and VIVEK HYBRID 11, bought by Rs. 30/- and 25/- per half kilogram from VPKAS, Almora, Regional Research Centre of ICAR. The experiment was conducted at the Seed Testing Laboratory of the Department of Seed Science and Technology, H.N.B. Garhwal University. The research comprised of determinations of seed water content, physical purity test, germination test, pure live seed per cent, seeding rate and determination of best buy value. Results revealed that same cost of both the seed lots of each variety is unreasonable due to variation in PLS per cent. Buying seeds from the seed lot 2 (S2) will give more benefit for both the varieties as their PLS% is high and respective cost prices are low but seeding rate was needed to increase for all seed lots from the recommended seed rate. From the study it may be suggested that such tests should be carried out by the seed testing laboratories as a security for the seed producers.